2016
DOI: 10.1108/ijchm-08-2014-0378
|View full text |Cite
|
Sign up to set email alerts
|

Insights into emotional contagion and its effects at the hotel front desk

Abstract: Purpose This paper aims to draw attention to the need for a nuanced view of the emotional contagion framework. It proposes and empirically tests a refined model of emotional contagion and its effects in the hotel sector by focusing on the front-desk service encounter interactions. Design/methodology/approach Data were collected from three separate groups of paired informants: receptionists, hotel customers and interaction observers. The sample included 573 full customer service interactions in 47 hotels in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 74 publications
1
27
1
1
Order By: Relevance
“…It is also assumed that happiness is particularly contagious (Chanes et al, 2018;Dimberg and Thunberg, 1998;Harker and Keltner, 2001;Lau, 1982). Findings in previous studies in a service context, in terms of interactions between employees and customers, do support that the customer's exposure to a happy employee can enhance the customer's own positive emotions (Li et al, 2018;Lee and Labroo, 2004;Ustrov et al, 2016). In the present study, it is assumed that this can also happen in a mediated context, in which a photo or a video represents the service firm employee.…”
Section: The Emotional Contagion Routesupporting
confidence: 47%
“…It is also assumed that happiness is particularly contagious (Chanes et al, 2018;Dimberg and Thunberg, 1998;Harker and Keltner, 2001;Lau, 1982). Findings in previous studies in a service context, in terms of interactions between employees and customers, do support that the customer's exposure to a happy employee can enhance the customer's own positive emotions (Li et al, 2018;Lee and Labroo, 2004;Ustrov et al, 2016). In the present study, it is assumed that this can also happen in a mediated context, in which a photo or a video represents the service firm employee.…”
Section: The Emotional Contagion Routesupporting
confidence: 47%
“…Scholars have shown that people often mimic or catch the emotions of others during their social interactions. 35 , 36 Social scientists have further demonstrated that people tend to copy the emotions of trusted or familiar people more readily. 37 This is called the trickle-down effect, which causes a transmitter’s affect and behavior to provoke similar responses in receivers.…”
Section: Theoretical Underpinning and Hypothesesmentioning
confidence: 99%
“…Müşterileri olumlu olarak etkilemek için hizmet sağlayıcılar olumlu duyguları yüz ifadelerinde göstermektedirler (Dallimore, Sparks ve Butcher, 2007). Hizmet sağlayıcılarının pozitif ve negatif duygu gösterimleri müşterilerin algıladığı hizmet kalitesini (Pugh, 2001) ve tatminini (Ustrov, Valverde ve Ryan, 2016) etkilemektedir. Bu durum pek çok hizmet işletmesinde "Güler yüzlü hizmet" olarak slogan haline gelmiştir.…”
Section: Müşteri-çalışan Etkileşimiunclassified